Anastomotic Ulcers: A Tertiary Centre Experience of Endoscopic Management Techniques. Issue 3 (28th September 2021) - Barraclough, Harriet; Girach, Ayesha; Rao, Prithviraj; Urs, Arun; Marven, Sean; Murthi, Govind; Thomson, Mike; Narula, Priya
Abstract : Supplemental Digital Content is available in the text Abstract : ABSTRACT: Improvements in neonatal care and surgical advances, has led to an increased prevalence of children with small and large bowel anastomoses. Ulceration at the site of anastomosis is a rare, but well-recognised phenomenon, with no clearly understood pathogenesis. Paediatric case series have been reported but there remains no clear effective treatment strategy and there is limited experience with endoscopic techniques in their management. We report our tertiary centre experience of managing nine anastomotic ulcer patients, including endoscopic treatment with argon plasma coagulation and clips. Two patients with inflammatory bowel disease (IBD) responded to optimisation of medical therapy. In our non-IBD patients, those requiring a blood transfusion (n = 2) ultimately required surgery and those who did not require a blood transfusion responded to aminosalicylate treatment (n = 1) or endoscopic therapeutic techniques (n = 3). We conclude that endoscopic interventions can be an effective management strategy for anastomotic ulcers when a blood transfusion isn't required.